Race and Reaction: Divergent Views of Police Violence and Protest against. (4th December 2017) - Reinka, Mora A.; Leach, Colin Wayne
Abstract: Since 2012, the United States has seen a renewed focus on police killings of racial and ethnic minorities, as well as protest against such violence. Moreover, recent polling data show an intensification of long‐standing differences in Black and White Americans' attitudes toward police violence and protest. Here, we review recent polling, as well as our own series of experiments, to elucidate racial divides in attention, attitudes, and reactions to police violence and protest against it (e.g., Black Lives Matter). In addition, we report linguistic analyses of descriptions ( N = 195) of protest images, showing that Black participants better understand the causes of these protests ( d = .30) and view them more positively ( d = .38) than Whites. If we wish for consensus on how to address police violence and protest against it, we must understand how and why the sociopolitical reality of race leads to divergent views of these issues.